PERADABAN DAN HASIL KEBUDAYAAN ISLAM DI ANDALUSIA PADA MASA DAULAH UMAYYAH - Nisaa', Intan Hafidhatun (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
This paper discusses Islamic civilization during the Umayyad State in Andalusia. The Umayyad State is the first Islamic caliphate after Khulafaur Rashidin or the second Islamic caliphate after the reign of Rasulullah SAW. The Umayyad State was founded by Muawiyah Ibn Abu Sufyan in 661 M in Damascus (as the center of his government). After the collapse of the Umayyad rule in Damascus, the Umayyad State succeeded in rising and ruling in Andalusia, with Abdurrahman ad-Dakhil as the first caliph. At first, this government was led by an amir, but during the reign of Abdurrahman III changed to caliph. When Islam entered Andalusia, the country experienced rapid progress both in terms of civilization and education. In the process of writing, the author uses a qualitative method by using literacy sources to collect the necessary data. Abstrak Tulisan ini membahas tentang peradaban Islam pada masa Daulah Umayyah di Andalusia. Daulah Umayyah adalah kekhalifahan Islam pertama setelah Khulafaur Rasyidin atau kekhalifahan Islam kedua setelah pemerintahan Rasulullah SAW. Daulah Umayyah didirikan oleh Muawiyah Ibn Abu Sufyan pada tahun 661 M di Damaskus (sebagai pusat pemerintahannya). Setelah runtuhnya pemerintahan Umayyah di Damaskus, daulah Umayyah berhasil bangkit dan berkuasa di Andalusia, dengan Abdurrahman ad-Dakhil sebagai khalifah pertama. Pada mulanya, pemerintahan ini dipimpin oleh seorang amir, namun ketika masa pemerintahan Abdurrahman III berubah menjadi khalifah. Ketika Islam memasuki Andalusia, negeri ini mengalami kemajuan yang pesat baik dari segi peradaban maupun pendidikannya. Dalam proses penulisannya, penulis menggunakan metode kualitatif dengan menggunakan sumber literasi untuk mengumpulkan data-data yang diperlukan.